Hospitalist and Primary Care Physician Perspectives on Medication Management of Chronic Conditions for Hospitalized Patients - Breu, Anthony C. (2014)
BACKGROUND: Little is currently known regarding physicians’ opinions on the relative appropriateness of inpatient management of medical conditions unrelated to the reason for admission. OBJECTIVE: Investigate physician attitudes on the appropriateness of inpatient medication interventions, based on the interventions’ relatedness to the reason for admission. DESIGN, SETTING, AND PARTICIPANTS: Case-based survey of hospitalists and hospital-based primary care physicians at three academic medical centers in Boston, Massachusetts. METHODS: Physicians were emailed a survey consisting of six pairs of clinical cases. Each pair included one case with an inpatient management decision related to the reason for admission followed by a case involving the same management decision, but unrelated to the reason for admission. Respondents rated the appropriateness of the interventions and results were compared based on the relatedness to the reason for admission and based on the respondents’ primary role. RESULTS: 162 out of 295 providers (55%) responded to the survey. Physicians were significantly more likely to rate inpatient interventions as appropriate when they were related, compared to unrelated, to the reason for admission (78.9% v. 38.8%; p<0.001). Primary care physicians were significantly more likely than hospitalists to feel that inpatient interventions were appropriate. (64.1% v. 52.1%, p <0.001; RR 1.3, 95% CI 1.1–1.4). CONCLUSION: Physicians are more likely to rate inpatient medication changes as appropriate when they are related to the reason for admission. Our results suggest that opportunities for meaningful medical interventions may be underutilized in current systems which adhere to a strict dichotomy of inpatient and outpatient roles.